Use of agroindustrial wastes as pozzolanic materials in cementitious systems: A review - Elias Rocha Gonçalves Júnior; Juliana Fadini Natalli; Marília Gonçalves Marques; Afonso Rangel Garcez de Azevedo; Markssuel Teixeira Marvila (Journal of Materials Research and Technology)
The construction industry consumes large amounts of energy and raw materials and is a significant source of atmospheric pollutants, primarily greenhouse gas emissions. Additionally, solid waste management poses a major challenge for society, given the diversity and quantity of waste, as well as population growth and consumption trends. An emerging alternative to mitigate these issues is the utilization of pozzolanic materials developed from waste. The paper aims to analyze the main types of ash from agro-industrial waste with potential for use as pozzolanic material. Materials commonly used and potential materials of interest were highlighted. Initially, searches were conducted in the Scopus database to find publications related to the use of agroindustrial waste ash as pozzolanic material in cement. The search terms were defined according to the topic at hand, resulting in 216 records. Of these records, over 70 % of the analyzed publications were published between 2008 and 2025, indicating a significant increase in the number of publications on the topic, which suggests a trend of growing interest in recent years, with India leading in publications. Subsequently, experimental data were presented to support the pozzolanic potential of four key waste ashes: rice husk ash (RHA), palm oil fuel ash (POFA), bamboo leaf ash (BLA), and sugarcane bagasse ash (SCBA). All materials demonstrated pozzolanic activity and contributed positively to cement-based systems. For instance, incorporating 20 % RHA led to an increase of up to 22 % in compressive strength at 28 days compared to the control mix. Similar improvements were observed with other ashes, depending on dosage and treatment conditions. These effects were generally more pronounced at later curing ages, reflecting the progressive nature of pozzolanic reactions. However, in some cases, high reactivity enabled strength gains to manifest as early as 7 days. The findings discussed in this paper may have significant implications for the construction sector, offering sustainable alternatives for waste valorization and reducing the environmental impact of cementitious materials.